The Effect of Variation of Push-Up Training on Extracurricular Volleyball Servis Skills - Dhimas Achmad Maldini; Khoirul Anwar; Heni Yuli Handayani (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
Extracurricular participants at SMPN 1 Tanah Merah basically haven't really mastered the basic technique of overhand service correctly and well, when they first saw playing they still didn't have good arm strength, so they had difficulty doing the overhand serve, so to improve their skills top service then requires an effective and efficient training method. This study aims to determine the effect of variations of push-up exercises on upper service skills in volleyball extracurricular activities at SMPN 1 Tanah Merah. This research is a quasi-experimental study using the one-group pretest-posttest design method with the top service test instrument. The data analysis technique used was the paired sample t-test, with the results of the t-test and t-table with a significant value of 0.00, t-count 24.80 > t-table 8.93 with a value of 0.00 <0.05. Thus the hypothesis states "There is an effect of variations in push-up exercises on upper service skills in the extracurricular activities of SMPN 1 Tanah Merah".